Burden of enteric fever and antibiotic sensitivity in Nepalese Children Prior to Typhoid Vaccine in National Immunization Program - Chapagain, Ram Hari; Adhikari, santosh; Bhattarai, Tribhuwan; Basaula, Yubanidhi; Bhattarai, Srijana (Journal of Nepal Health Research Council, 2023)
Background: Enteric fever is a major public health problem in developing and under developed countries. Case fatality rate without treatment is 10-30% and with appropriate treatment is only 1-4%. Gold standard for diagnosis is isolation of Salmonella enterica from blood or bone marrow. Antibiotics resistance is skyrocketing with emergence of multidrug resistance S. typhi and extensively drug resistant S. typhi. Methods: The blood culture done in Kanti children hospital in last six years were taken from the data base and the culture positive cases were taken from which the salmonella species positive cases along with the drug sensitivity pattern were used in our study. Results: The culture positivity rate was 2.8% and 7.6% (n=136) among the culture positive cases were Salmonella species. Salmonella typhi (121; 88.9%) was the most frequently isolated species, followed by Salmonella paratyphi A (13; 9.5%) and Salmonella paratyphi B (2;1.4%). Children with age 5-10 years was the most affected age group for infection with Salmonella, 50.0% (n=68). Nalidixic acid is resistant in 89.9% Salmonella typhi; followed by ciprofloxacin (31.8%), ofloxacin (18.2%), ampicillin (9.6%), azithromycin (8.4%), chloramphenicol (8.2%), cotrimoxazole (5.4%), cefixime (4%), ceftriaxone (2.5%) and cefotaxime (0.0%). Cefixime, ceftriaxone, cefotaxime are 100% sensitive to Salmonella paratyphi, followed by cotrimoxazole (92.9%), ofloxacin (81.8%), chloramphenicol (75%), azithromycin (66.7%), ampicillin (60%), ciprofloxacin (50%) and Nalidixic acid (23.1%). Conclusions: Salmonella species culture isolatation are declining every year. Fluoroquinolones have more resistance than first line drugs of typhoid, azithromycin resistance is rising but 3rd generation cephalosporins are sensitive to Salmonella species. Keywords: Drug sensitivity; enteric fever; salmonella paratyphi; salmonella typhi; typhoid vaccine